Measuring amplitude and phase distribution of fields generated by gratings with sub-wavelength resolution - Nesci, A.; Dändliker, René; Salt, M.; Herzig, Hans-Peter (My University, 2002)
In this paper, we intend to gain an understanding of the interaction of light with microstructures. Measurements of amplitude and phase in the diffracted field close to gratings using a heterodyne scanning probe are presented. Coherent light diffracted by microstructures produces periodic features and can give birth to phase dislocations, also called phase singularities. Phase singularities are isolated points where the amplitude of the field is zero. We present measurements of such phase singularities with 10 nm spatial sampling and compare them with theoretical results obtained from rigorous diffraction calculations. The observed polarization effects reveal also important information about the vectorial field conversion by the fiber tip.